2020
DOI: 10.1108/srj-01-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Social and environmental disclosure of the largest companies in Brazil’s agribusiness sector

Abstract: Purpose Brazil’s agribusiness sector is an acknowledged and relevant player in international markets. Companies operating in this industry have been closely observed by society with increasingly critical judgment relating to production systems and the impact of these companies. In this context, this study aims to assess the voluntary disclosure of social and environmental information of Brazilian agribusiness companies and test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 63 publications
0
2
0
6
Order By: Relevance
“…(5) listrik; (6) distribusi gas dan air (Dias et al, 2019;Brown & Deegan, 1998). Kedekatan konsumen diukur menggunakan variabel dummy, dimana 1 untuk perusahaan high-visibility dan 0 untuk perusahaan low-visibility (Branco & Rodrigues, 2008;Dias et al, 2019;Gupta & Kumar, 2021;Ismail et al, 2018;Santos et al, 2021).…”
Section: Kedekatan Konsumenunclassified
“…(5) listrik; (6) distribusi gas dan air (Dias et al, 2019;Brown & Deegan, 1998). Kedekatan konsumen diukur menggunakan variabel dummy, dimana 1 untuk perusahaan high-visibility dan 0 untuk perusahaan low-visibility (Branco & Rodrigues, 2008;Dias et al, 2019;Gupta & Kumar, 2021;Ismail et al, 2018;Santos et al, 2021).…”
Section: Kedekatan Konsumenunclassified
“…This paper inclines the legitimacy theory, positing that companies that pollute use social responsibility to appease and divert community and stakeholder activities on corporate environmental responsibility (Feng et al, 2020). Hence, the legitimacy theory's central precept is that companies adopt a strategic approach to finding congruence between societal pressure and organizational goal (Deegan, 2019;Dos Santos et al, 2020). Given that the corporate's primary aim is profit, some companies in developing countries with a weak policy on environmental pollution try to legitimize their polluting operations by feigning responsible corporate by reporting what the communities would like to see (Dube and Maroun, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Notwithstanding, and as in other places in the world, it has been suggested that various negative externalities generated due to the expansion and intensification of agricultural production cause environmental impacts [4] and raise questions about inequalities in the distribution of government benefits [5]. Thus, the current agricultural production model has been harshly criticized [6], leading to analyses being developed to understand better the interconnections between agricultural activities, the use of environmental resources, and social aspects as a whole [7,8]. Currently, in response to the growth of socio-environmental and economic concerns, the themes "sustainability" and "agricultural production" have aroused the interest of several scientists and researchers around the world [9].…”
Section: Introductionmentioning
confidence: 99%